TkSRPP3/4 interactors TkGGR1 and TkLIL3 link plastid-like organelles with isoprenoid metabolism in Taraxacum koksaghyz latex - Silva Melissa Wolters; Lukas Schwarz; Ronja Khairat; Kristina Sturm; Boje Müller; Nicole van Deenen; Richard M. Twyman; Dirk Prüfer; Christian Schulze Gronover (Plant Cell Reports, 2025)
Key message The presence of plastid-like structures in the latex of the Russian dandelion Taraxacum koksaghyz and interactions involving plastid-associated TkGGR1 with TkSRPP3, TkGGPS6 and TkLIL3 may confer TkSRPP-mediated stress tolerance. Abstract The latex of the Russian dandelion Taraxacum koksaghyz is a rich source of natural rubber (NR) but other facets of its metabolism and physiology have been largely neglected. Small rubber particle proteins (SRPPs) contribute to NR biosynthesis by stabilizing rubber particles and are also linked to stress responses. The identification of geranylgeranyl reductase (GGR1) as potential interactor of TkSRPP3 in our previous study prompted its detailed investigation because GGRs normally reduce geranylgeranyl groups to phytol or phytyl diphosphate for chlorophyll synthesis in chloroplasts. Here we determined the latex-specific expression and phytol-producing activity of GGR1, and confirmed its interaction with TkSRPP3. Metabolic analysis of plants with altered TkGGR1 expression levels in latex revealed its involvement in tocopherol but not NR synthesis in roots, whereas a second, leaf-specific GGR was responsible for chlorophyll synthesis. We found that a geranylgeranyl diphosphate synthase (GGPS) and light-harvesting-like 3 protein (LIL3) were co-expressed in latex and translocated into Nicotiana benthamiana chloroplasts, as we also observed for TkGGR1. We confirmed that TkGGR1 interacted with TkGGPS6 and TkLIL3 inside chloroplasts and detected an extraplastidial interaction between TkLIL3 and TkSRPP4. In situ analysis of mVenus-tagged TkGGR1 indicated its localization in plastid-like structures in T. koksaghyz latex, which lacks conventional chloroplasts. We therefore hypothesized the presence of a TkGGR1-containing multiprotein complex within Frey–Wyssling-like particles in latex that may confer oxidative stress tolerance. This study provides insight into a previously undescribed branch of isoprenoid metabolism and cellular biology of NR-producing laticifers in T. koksaghyz .